Kisi-Kisi Soal Sebagai Instrumen Evaluasi Pendidikan: Tinjauan Teoretis, Ragam Instrumen, dan Tantangan Implementasi di Sekolah - Gerry Mandala (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
In the education system, learning evaluation plays a fundamental role in measuring students' academic competency achievement. This study was designed to comprehensively examine the importance of high-quality learning instruments and the strategic role of assessment frameworks in ensuring the instrument's alignment with the formulated learning objectives. A qualitative, descriptive approach based on a literature review was used. The study's findings indicate that assessment frameworks serve as a framework or blueprint capable of validly and reliably mapping competencies, material coverage, and assessment weighting. Systematic implementation of assessment frameworks has been proven to increase the transparency and accountability of evaluations, while also supporting educators in integrating Islamic values ​​into the context of Islamic Religious Education (PAI). However, its implementation still faces obstacles, including limited teacher competency in developing Higher Order Thinking Skills (HOTS)-based questions, as well as constraints related to time and resource availability.